MOLECULAR CHARACTERIZATION OF SUGARCANE (SACCHARUM OFFICINARUM L.) GENOTYPES IN RELATION TO SALT TOLERANCE - N. R. MARKAD; A. A. KALE; B. D. PAWAR (The Bioscan, 2014)
This study was conducted to characterize the salt tolerant and susceptible genotypes (F1s) of sugarcane by 15 ISSR primers. The amplification profile consisted of 118 fragments of size ranging from 275 bp to 2845 bp of which 28 were monomorphic and 82 were polymorphic with 69.49 % polymorphism. The number of bands generated by each primer varied from 4 (ISSR -823) to 11 (ISSR–809, ISSR–824 and ISSR-830) with an average of 8.4 fragments per primer. The percentage of polymorphic bands with different primers ranged from 50 to 88.88 %. The efficiency of ISSR marker for cultivar identification was found 6.8 % as only eight fragments are cultivar specific.PIC values were ranged from 0.47 (ISSR 830) to 0.88 (ISSR 816) primers with an average value of 0.70. Rp values were ranged from 2.40 (ISSR 823) to 11.86 (ISSR 809) primers with an average value of 6.18. The similarity coefficients detected by ISSR ranged from 0.65 to 0.84 which revealed existence of limited genetic variation among sugarcane genotypes. In the consensus tree thesalt-tolerant genotypes cluster together indicating the efficiency of ISSR markers to differentiate between tolerant and susceptible genotypes based on their similarity matrix.Our study has established that the ISSR markers are useful for studying genetic diversity among sugarcane and thereby helps in selecting superior crosses and for distribution genotypes into different groups.